Syndecan-1 Acts as an Important Regulator of CXCL1 Expression and Cellular Interaction of Human Endometrial Stromal and Trophoblast Cells - Dunja Maria Baston-Buest; Olga Altergot-Ahmad; Sarah Jean Pour; Jan-Steffen Krüssel; Udo Rudolf Markert; Tanja Natascha Fehm; Alexandra Petra Bielfeld (Hindawi Limited, 2017)
Successful implantation of the embryo into the human receptive endometrium is substantial for the establishment of a healthy pregnancy. This study focusses on the role of Syndecan-1 at the embryo-maternal interface, the multitasking coreceptor influencing ligand concentration, release and receptor presentation, and cellular morphology. CXC motif ligand 1, being involved in chemotaxis and angiogenesis during implantation, is of special interest as a ligand of Syndecan-1. Human endometrial stromal cells with and without Syndecan-1 knock-down were decidualized and treated with specific inhibitors to evaluate signaling pathways regulating CXC ligand 1 expression. Western blot analyses of MAPK and Wnt members were performed, followed by analysis of spheroid interactions between human endometrial cells and extravillous trophoblast cells. By mimicking embryo contact using IL-1β, we showed less ERK and c-Jun activation by depletion of Syndecan-1 and less Frizzled 4 production as part of the canonical Wnt pathway. Additionally, more beta-catenin was phosphorylated and therefore degraded after depletion of Syndecan-1. Secretion of CXC motif ligand 1 depends on MEK-1 with respect to Syndecan-1. Regarding the interaction of endometrial and trophoblast cells, the spheroid center-to-center distances were smaller after depletion of Syndecan-1. Therefore, Syndecan-1 seems to affect signaling processes relevant to signaling and intercellular interaction at the trophoblast-decidual interface.